2012
DOI: 10.1007/s10592-012-0401-7
|View full text |Cite
|
Sign up to set email alerts
|

Landscape heterogeneity and local adaptation define the spatial genetic structure of Pacific salmon in a pristine environment

Abstract: Identifying the spatial distribution of genetic variation across the landscape is an essential step in informing species conservation. Comparison of closely related and geographically overlapping species can be particularly useful in cases where landscape may similarly influence genetic structure. Congruent patterns among species highlight the importance that landscape heterogeneity plays in determining genetic structure whereas contrasting patterns emphasize differences in species-specific ecology and life-hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 57 publications
0
14
0
Order By: Relevance
“…; Ackerman et al . ), while others have found that patterns of MHC differentiation are consistent with neutrality (e.g. Seddon & Baverstock ; Campos et al .…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…; Ackerman et al . ), while others have found that patterns of MHC differentiation are consistent with neutrality (e.g. Seddon & Baverstock ; Campos et al .…”
Section: Introductionmentioning
confidence: 95%
“…For example, multiple studies have found that MHC differentiation among populations is larger than would be expected under a model of neutrality or balancing selection (e.g. Ekblom et al 2007;Gomez-Uchida et al 2011;Ackerman et al 2013), while others have found that patterns of MHC differentiation are consistent with neutrality (e.g. Seddon & Baverstock 1999;Campos et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Functional genetic markers, like the ones used in this study, reveal important genetic differences among populations that may not be evident based solely on neutral genetic markers. For example, putatively adaptive SNPs have revealed population structure patterns that were not evident for neutral loci in salmonids (Ackerman, Templin, Seeb, & Seeb, ; Hand et al., ; O'Malley, Jacobson, Kurth, Dill, & Banks, ) and invasive invertebrates (Rohfritsch et al., ; Tepolt & Palumbi, ). More importantly, the functions of such genes can reveal important information about the environmental or ecological forces driving genetic differences among populations.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, locally adapted MHC alleles may exist leading to greater population differentiation (Muirhead 2001). To date, studies have found that, compared to neutral markers, MHC differentiation can be (i) greater than expected suggesting local adaptation (Ekblom et al 2007;Loiseau et al 2009;Ackerman et al 2013;Kyle et al 2014), (ii) weaker than expected consistent with balancing selection (Sommer 2003;Fraser et al 2010;Strand et al 2012) or (iii) not different than neutral markers suggesting weak selection or a strong effect of drift (Miller et al 2010;Zeisset & Beebee 2014). These differences in results may be related to the relative effects of gene flow, drift and selection (Bryja et al 2007) and the spatial scale of the study (Landry & Bernatchez 2001;Herdegen et al 2014).…”
Section: Introductionmentioning
confidence: 96%
“…; Ackerman et al . ; Kyle et al . ), (ii) weaker than expected consistent with balancing selection (Sommer ; Fraser et al .…”
Section: Introductionmentioning
confidence: 99%